2010
DOI: 10.2319/050410-66.1
|View full text |Cite
|
Sign up to set email alerts
|

Cephalometric craniofacial features in Saudi parents and their offspring

Abstract: Objective: To estimate the correlation and heritability values of craniofacial variables between parents and their offspring. Materials and Methods: The sample comprised 24 Saudi families; each family consisted of father, mother, son, and daughter. Lateral cephalometric radiographs were taken for each family member. Twenty-eight angular, linear, and proportional cephalometric variables were measured. Interfamilial correlations and heritability (h 2 ) values were estimated among father-son, father-daughter, mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
12
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 20 publications
4
12
0
1
Order By: Relevance
“…This result is in accordance with the results of a previous study [35]. In general, there were more correlations and higher h 2   values in the father-offspring groups than in the mother-offspring groups.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result is in accordance with the results of a previous study [35]. In general, there were more correlations and higher h 2   values in the father-offspring groups than in the mother-offspring groups.…”
Section: Discussionsupporting
confidence: 93%
“…In general, there were more correlations and higher h 2   values in the father-offspring groups than in the mother-offspring groups. This result is consistent with the results of other studies [35, 36]. However, there is a study that does not confirm our results which found no significant difference in the value of any parents-offspring correlations [8].…”
Section: Discussionsupporting
confidence: 86%
“…Previous estimates of the heritability of facial shape distances and angles were principally derived by direct measurements between common facial morphometric landmarks on human faces, cephalograms, and skulls. These estimates vary widely; in general, facial height dimensions tend to be more heritable than width (Manfredi et al 1997;Carson 2006;Amini and Borzabadi-Farahani 2009;AlKhudhairi and AlKofide 2010), in contrast with the rest of the skull, for which heritability of width tends to be greater than for height (Martínez-Abadías et al 2009a,b, 2012.…”
mentioning
confidence: 99%
“…The strong facial resemblance among close relatives, and the high heritabilities of many facial measurements [26], underscore a major genetic component underlying facial shape. It is clear that aging and environmental factors such as nutrition also play large roles in facial shape.…”
Section: Discussionmentioning
confidence: 99%
“…While facial variation is subject to environmental modifiers such as age and nutritional status, striking facial similarities within families suggest a strong genetic component [1], and heritability of some facial measurements is as high as 94% [26]. …”
Section: Introductionmentioning
confidence: 99%